Mr. Penguin and the lost treasure - Smith, Alex T. (London: Hodder Children's Book, 2017)
Aspiring Professional Adventurer Mr. Penguin and his colleague, Colin the spider, try to find a treasure rumored to be buried in The Museum of Extraordinary Objects before bandits do.
Booklist starred
Kirkus Review
School Library Journal
Booklist starred, March 2019
Kirkus Review, January 2019
Library Media Connection, March 2019
Keywords: Adventure stories; Detective and mystery stories; Museums -- Juvenile fiction; Penguins -- Juvenile fiction; Spiders -- Juvenile fiction; Thieves -- Juvenile fiction; Treasure troves -- Juvenile fiction; Adventure and adventurers -- Fiction; Buried treasure -- Fiction; Museums -- Fiction; Mystery and detective stories; Penguins -- Fiction; Robbers and outlaws -- Fiction; Spiders -- Fiction; Adventure fiction; Buried treasure -- Fiction; Museums -- Fiction; Mystery fiction; Penguins -- Fiction; Spiders -- Fiction; Thieves -- Fiction; Action and adventure fiction; Detective and mystery fiction